The First 2D Homochiral Lead Iodide Perovskite Ferroelectrics [R- and S-1-(4-Chlorophenyl)ethylammonium]2 PbI4 - Yang, Chen-Kai (Advanced materials (Deerfield Beach, Fla.), 2019)
© 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.